Measurement of spin density matrix elements in Λ(1520) photoproduction at 8.2-8.8 GeV; Physical Review C; Vol. 105, iss. 3 - Adhikari Sh. Shankar; Akondi C. S.; Albrecht M.; Ali A.; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich (2022, 2022)
Title screen